THE DIFFICULTIES OF TRANSLATION TERMS IN THE SPHERE OF GEOLOGY FROM ENGLISH INTO UZBEK - Rikhsieva Lola Azimjanovna, (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This scientific research describes the problems encountered in the translation of terms and texts related to the field. This article reflects problems such as usage of various fields, polysemy and differences from typological aspect point views that are relevant for some translators when translating geological terms.